Pengaruh Pengendalian Audit Internal dan Independensi Auditor Terhadap Pencegahan Kecurangan - Rina Marfiana; Muji Gunarto (Jurnal Bisnis, Manajemen, dan Ekonomi, 2021)
The objective of the study is to determine whether internal audit control and auditor independence affect corruption prevention at PT. Bank Sumsel Babel, either partially or simultaneously, As well as to know what is the most influencial variable in preventing corruption. The study used a population with a total of 135 respondents. The data collection technique used was by distributing questionnaires. The independent variables used in the study were internal audit control and auditor independence, while corruption prevention was the dependent variable. The results of the study indicate that partially, the variable of internal audit control and auditor independence have a significant effect to corruption prevention. The study explained that the independent variable has a significant effect towards the dependent variable